Induced Breeding and Management Practices for Mass Seed Production of Nutrition-Sensitive Tengara Catfish (Mystus tengara) - Ali, Hazrat; Dubey, Sourabh; Biswas, Ashutosh; Jaman, Ahmed; Rashid, Harun (WorldFish, 2024)
The practical guideline ‘Induced Breeding and Management Practices for Mass Seed Production of Nutrition-Sensitive Tengara Catfish (Mystus tengara)’ has been developed under the CGIAR Initiative on Asian Mega-Deltas. This comprehensive manual provides a user-friendly, step-by-step protocol for the induced breeding of Tengara catfish, addressing the lack of standardized techniques that previously constrained its widespread adoption. It also includes detailed guidance on seed nursery management, packaging, and transportation systems, ensuring effective seed production and distribution. The nine-step process is tailored for easy implementation by fish hatcheries, supporting the expansion of nutrition-sensitive aquaculture practices. By facilitating the sustainable scaling of Tengara catfish production, this guideline contributes to improving food security in regions where the species holds significant nutritional importance.